Odpowiedzi

  • Użytkownik Zadane
2009-10-31T23:46:25+01:00
1. (x+y)*a+(x+y)*b=(x+y)(a*b)

2, 3(2-y)-a(2-y)=(2-y)(3-a)

3, (m-1)(k_1)+(k-1)(m+1)=(k-1)(m-1+m+1)=(k-1)(2m)

4, (a-1)(b+c)-(a-1)(b-c)(a-1)(b+b-c)=(a-1)(2b)

5, -4x+2y-7-3x+7=-7+2y

6,
0,1x+0,2=-0,3
0,1x=-0,3-0,2
0,1x=-0,5/0,1
x=-5
2009-10-31T23:54:55+01:00
A) (x+y)*a+ (x+y)* b = ax+ay+bx+by

b) 3(2-y)-a(2-y)= 6-3y-2a+ay

c) (m-1)(k-1)+(k-1)(m+1)= km-m-k+1+km+k-m-1=2km-2m

d) (a-1)(b+c)-(a-1)(b-c)= ab+ac-b-c-ab+ac-b+c=2ac-2b

e) -4x+2y-7-3x+7= -7x+2y ( 7 się redukują)

f) 0,1x+0,2=-0,3
0,1x= -0,3-0,2
0,1x= -0,5 / 0,1
x= -5
2009-10-31T23:57:11+01:00
(x+y)*a+(x+y)*b=(x+y)(a*b)

3(2-y)-a(2-y)=(2-y)(3-a)

(m-1)(k_1)+(k-1)(m+1)=(k-1)[(m-1)+(m+1)]=2m(k-1)

(a-1)(b+c)-(a-1)(b-c)=(a-1)[(b+c)-(b-c)]=2c(a-1)

-4x+2y-7-3x+7=-7x+2y

0,1x+0,2=-0,3
0,1x=-0,3-0,2
0,1x=-0,5
x=-5